PENDAMPINGAN PEMBENTUKAN DAN PENGUATAN TIM PELAKSANA PROGRAM KETAHANAN PANGAN DALAM MENDUKUNG KEMANDIRIAN DESA NAINGGOLAN DAN JANJI MARAPOT - Hadasah Nababan; Nancy Nopeline (DEVELOPMENT: Journal of Community Engagement, 2026)
This community service program was conducted in Nainggolan Village and Janji Marapot Village, Nainggolan District, Samosir Regency, focusing on strengthening village food security through the formation of a Village Activity Implementation Team (TPK). This topic was chosen because both villages are agrarian in nature with limited infrastructure, extreme dry climate conditions, and challenges in water access and agricultural product distribution, necessitating planned and institutional-based food security management. The community service method involved field observation, participation in village meetings, and assistance in the formation and strengthening of the Food Security TPK institution. The results of the activity showed that the formation of the TPK, involving community members and village officials, increased participation and transparency in Village Fund management, and encouraged the development of productive village businesses, particularly in the poultry farming sector. This program also has the potential to be developed through cross-program collaboration to strengthen the village's economic sustainability and food security. These findings emphasize the importance of an institutional approach in village-based food security development.